2006
DOI: 10.2298/hel0644065p
|View full text |Cite
|
Sign up to set email alerts
|

Wild sunflowers research in Argentina

Abstract: Since 2000 a research is in progress on wild sunflowers in Argentina, comprising naturalized H. annuus and H. petiolaris populations, and their relationship with cultivated sunflower. The study includes morphological, phenological, biochemical and molecular aspects, addressed to explain dispersal and adaptive processes and gene flow within sunflower crop. We present here a summary of results obtained during the last five years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
0
3
0
2
Order By: Relevance
“…Contrary to this, Brighenti et al [29] found that nicosulfuron had no phytotoxic effect on sunflower crops. It may not be possible to extrapolate the results of these studies to the populations of weedy sunflower due to the high morphological and genetic variability of different sunflower forms [30][31][32][33]. Owing to the distinct morphological and genetic variations of weedy sunflower, which include different proportions of cultivated and wild traits, a very different response of its populations to herbicides can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to this, Brighenti et al [29] found that nicosulfuron had no phytotoxic effect on sunflower crops. It may not be possible to extrapolate the results of these studies to the populations of weedy sunflower due to the high morphological and genetic variability of different sunflower forms [30][31][32][33]. Owing to the distinct morphological and genetic variations of weedy sunflower, which include different proportions of cultivated and wild traits, a very different response of its populations to herbicides can be expected.…”
Section: Introductionmentioning
confidence: 99%
“…Male-sterile source from Mendoza province (Poverene et al, 2006) was characterized in ten F 1 generations obtained by controlled crosses with six restorers inbred lines (R49, R307, R432, RMAX1, RHA274, RPET2), three maintainer inbred lines (HA89B, B09, B10), and fertile plants of the same wild population. F 1 plants were considered male-fertile when they produced abundant pollen, while plants without anthers or visible pollen were classified as male-sterile.…”
Section: Methodsmentioning
confidence: 99%
“…The male sterile source found in LMA (Poverene et al, 2006) was restored by the maintainer (B) lines B10, HA89 B and B09 for the PET1 cytoplasm. The latter produced 96% fertile progeny in the F 1 generation ( Figure 5).…”
Section: Male Sterility and Fertility Restorersmentioning
confidence: 99%
“…Aunque por otro lado, otros autores trabajando con girasol silvestre en Argentina, indican que el diámetro del tallo se ha correlacionado de manera directa y significativa con el peso y número de semillas (Poverene et al, 2006), por lo que la selección para el rendimiento podría basarse en estos caracteres.…”
Section: Resultados Del Diámetro Del Tallo En La Planta De Girasolunclassified
“…Se observa que la altura de la planta de girasol se relaciona positivamente con el diámetro del tallo, el diámetro del capítulo, el peso de las 1000 semillas, el rendimiento del aceite y el contenido en ácido graso oleico en el aceite. Estos resultados se contradicen con los obtenidos por Sanchez y coinciden con los de Poverene et al (2006), incidiendo que la altura de planta se relacionan positivamente con el tamaño del capítulo sobre todo en cultivos de girasol con aportes nitrogenados muy altos. Y la altura de la planta se relaciona también con el resto de parámetros vegetativos, en la obtención de aceite.…”
Section: Relaciones Entre Variables Para El Cultivo De Girasolunclassified